Correlated evolution of beak morphology and song in the neotropical woodcreeper radiation. - Derryberry, E; Seddon, N; Claramunt, S; Tobias, J; Baker, A; Aleixo, A; Brumfield, RT (2012)
Mating signals may diversify as a byproduct of morphological adaptation to different foraging niches, potentially driving speciation. Although many studies have focused on the direct influence of ecological and sexual selection on signal divergence, the role of indirect mechanisms remains poorly understood. Using phenotypic and molecular datasets, we explored the interplay between morphological and vocal evolution in an avian radiation characterized by dramatic beak variation, the Neotropical woodcreepers (Dendrocolaptinae). We found evidence of a trade-off between the rate of repetition of song syllables and frequency bandwidth: slow paced songs had either narrow or wide frequency bandwidths, and bandwidth decreased as song pace increased. This bounded phenotypic space for song structure supports the hypothesis that passerine birds face a motor constraint during song production. Diversification of acoustic characters within this bounded space was correlated with diversification of beak morphology. In particular, species with larger beaks produced slower songs with narrower frequency bandwidths, suggesting that ecological selection on beak morphology influences the diversification of woodcreeper songs. Because songs in turn mediate mate choice and species recognition in birds, these results indicate a broader role for ecology in avian diversification.